Optimization for extraction on total phenolic contentand radical scavenging capacity of henna (Lawsonia inermis) stems using response surface methodology - Tan, Mun Chieng; Tan, Chin Ping; Khoo, Hock Eng; Ho, Chun Wai (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2014)
This study aimed to optimise potential extraction conditions using response surface methodology (RSM) for yielding maximum levels of total phenolic content (TPC) and 2,2-diphenyl-1-picryhydrazyl radical (DPPH•) scavenging capacity of henna (Lawsonia inermis) stems. The ranges for selected independent variables, namely acetone concentration (20-90%, v/v), extraction time (10-90 min) and extraction temperature (25-45°C) were identified by screening tests. Optimum conditions obtained for extraction of TPC were 47.0% acetone, extraction time of 47.6 min and extraction temperature of 37.3°C. The result also showed that 75.8% acetone, extraction time of 26.2 min and extraction temperature of 41°C yielded the highest DPPH• scavenging capacity. The optimized extraction conditions have resulted in TPC and DPPH• scavenging capacity of 5232.4 mg GAE/100 g DW and 6085.7 g TE/100 g DW, respectively which similar to the predicted values. Therefore RSM has successfully optimized the extraction conditions for TPC and radical scavenging capacity of henna stems.